Ruderal vegetation of Ukraine. Class Artemisietea vulgaris Lohmeyer et al. in Tx. ex von Rochow 1951 - Dubyna, Dmytro; Iemelianova, Svitlana; Dziuba, Tetiana; Davydov, Denys; Davydova, Anastasia; Tymoshenko, Pavlo (Biodiversity research and conservation, 2023)
The syntaxonomical diversity of the ruderal vegetation of the class in the territory of Ukraine has been studied in 2015-2020. It is established that this class includes 58 associations from six alliances ( , , , , and ) and two orders ( and ). Based on the results of the DCA-ordination analysis, it was found that the distribution of this type of ruderal vegetation is determined by the concentration of mineral nitrogen, the degree of aeration of the substrate, and the variability of moisture. At the level of high-rank syntaxa we didn’t find only vegetation that was specific for sub-Mediterranean and Mediterranean regions as well as for eastern part of European russia. At the same time, we determined specific vegetation on the European scale from the territory of Ukraine. This is Crimean submediterranean xero-mesophytic ruderal vegetation and semiruderal meso-xerophytic vegetation united into two alliances – and . All associations within these alliances are also specific only for the territory of Crimea, characterized by the specific floristic structure and diagnostic species core, and didn’t find in other regions of Ukraine.